Error Analysis Towards Recount Text Written By The Eighth-Grade Students Of SMPIT Qurrata A’yun Batusangkar - Chair, Hafizul; Yelliza, Merri; Febrianto, Romi (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2024)
The research aims to identify the types of syntactic in recount texts by the eighth-grade students of SMPIT Qurrata A'yun Batusangkar. In addition, it is crucial to know the frequency of each type of error, the dominant type of error, and the sources of the errors. The type of research is qualitative research. The method of collecting data is the elicitation method, which is divided into four steps: the first step is requesting the learner to make a recount text with the theme that has been given; the second step is reading the recount text made by students; the third step is finding and marking errors in the recount text; and the last step is dividing the errors into types based on linguistic category and surface strategy taxonomy. The dominant type of error is wrong spelling and misuse of a verb in the past tense. Besides, the findings and results demonstrated that students' English writing skill, especially in recount text, demands more attention, improvement, and development. The recommendations and pedagogical implications recognize the critical role of EFL teachers, curriculum designers, educators, and policymakers in achieving the desired results.